Illustrating a novel methodology and paradigm applied to Emergency Department research. (30th August 2021) - Binnie, Vicki; Le Brocque, Robyne; Jessup, Melanie; Johnston, Amy N. B.
Abstract: Aim: To provide a practical example of how a novel methodology and paradigm was applied to a mixed methods study exploring the healthcare experiences of Australian adults who frequently use emergency department services. Design: Discussion Paper. Data sources: We explored published literature discussing philosophical and methodological issues related to mixed methods research. Literature searches were performed between July 2019 and February 2021. Implications for nursing: Phenomenology is a powerful methodology to explore the lived experience of research participants, but it is not without limitations. Mixed methods phenomenology allows nurse researchers to bring further clarity to their research phenomena, however, including phenomenology in mixed methods studies may be seen to be philosophically incompatible. The philosophical metaparadigm of dialectical pluralism provides nurse researchers with a new coherent methodological and philosophical framework for combining participants' descriptions of lived experience with a variety of data collection methods. It is effective when working with transdisciplinary research teams, and stakeholders representing diverse values and disciplines. Conclusion: Complex healthcare environments require sophisticated, flexible research approaches. This paper presents mixed methods phenomenological research combined with the metaparadigm of dialectical pluralism providing a methodological framework that can support multifaceted nursing research. Impact: The combination of mixed methods phenomenology and dialectical pluralism represents a novel solution for nurse researchers to articulate a research methodology and philosophical paradigm reflecting the complexity embedded in everyday nursing practice. This methodology offers a unique approach to exploration of challenging clinical and patient scenarios with multifaceted elements, and overcomes theories of philosophical incompatibilities between divergent methods.